2014
DOI: 10.1016/j.cell.2014.10.015
|View full text |Cite
|
Sign up to set email alerts
|

A Widespread Glutamine-Sensing Mechanism in the Plant Kingdom

Abstract: Glutamine is the primary metabolite of nitrogen assimilation from inorganic nitrogen sources in microorganisms and plants. The ability to monitor cellular nitrogen status is pivotal for maintaining metabolic homeostasis and sustaining growth. The present study identifies a glutamine-sensing mechanism common in the entire plant kingdom except Brassicaceae. The plastid-localized PII signaling protein controls, in a glutamine-dependent manner, the key enzyme of the ornithine synthesis pathway, N-acetyl-l-glutamat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
189
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(221 citation statements)
references
References 62 publications
10
189
1
Order By: Relevance
“…A recombinant form of A. thaliana P II containing a functional Q loop from C. reinhardtii exhibited glutamine dependency in the NAGK interaction, confirming that the plant-specific C-terminal extension mediates the glutamine response. These observations suggest that glutamine sensing is a conserved feature of P II signaling in most plant chloroplasts (154).…”
Section: -Og Signaling In Eukaryotesmentioning
confidence: 82%
See 1 more Smart Citation
“…A recombinant form of A. thaliana P II containing a functional Q loop from C. reinhardtii exhibited glutamine dependency in the NAGK interaction, confirming that the plant-specific C-terminal extension mediates the glutamine response. These observations suggest that glutamine sensing is a conserved feature of P II signaling in most plant chloroplasts (154).…”
Section: -Og Signaling In Eukaryotesmentioning
confidence: 82%
“…Surprisingly, however, a recent study revealed that the structural features of P II proteins from members of the Brassicaceae, such as A. thaliana, are atypical compared with those found in most of the plant kingdom. In contrast to A. thaliana, green plant and algal P II proteins contain a plant-specific C-terminal extension that forms a novel loop in the structure, termed the Q loop, which confers a low-affinity glutamine binding site (154). In vitro studies with Chlamydomonas reinhardtii P II demonstrated that it binds NAGK in a glutamine-dependent manner, in addition to the 2-OG-regulated interaction.…”
Section: -Og Signaling In Eukaryotesmentioning
confidence: 99%
“…Provided cycling glutamine constitutes a systemic signal, the down-regulation of nitrate uptake would require homeostasis between the cycling pool of glutamine and the glutamine pool at the site of nitrate uptake as a means to monitor the whole plant N status by the roots. Recently, a cellular mechanism of glutamine-sensing has been identified that seems to be widespread in the plant kingdom [78]. The plastid-localized PII signaling proteins can sense and integrate metabolic signals by conformational changes, thereby exerting control at all levels of metabolic regulation, including transport activity, metabolic reactions and gene expression.…”
Section: Regulation Of N Acquisition and Distribution In Treesmentioning
confidence: 99%
“…Gln is the primary product of nitrogen assimilation in plants and a central metabolite of nitrogen metabolism. Although as yet unknown, a Gln-sensing mechanism similar to that recently identified in other plant families (Chellamuthu et al, 2014) could play a pivotal role in coordinating nitrogen metabolism in response to the general metabolic state of the cell. In this regard, Gln along with Asn are the main organic nitrogen forms transported between roots and the AP.…”
Section: Metabolite and Gene Targets Of Gapcp Activitymentioning
confidence: 99%